Imaging in Diabetes Mellitus - Rajul Rastogi; Sujeet Kumar Jain (Archives of Clinical Nephrology - Peertechz Publications, 2016)
Diabetes mellitus [DM] is the commonest endocrine disorder encountered in the clinical practice. It in fact, comprises of multiple disorders that manifest in the form of hyperglycemia. It is a multisystem disorder with pathophysiologic changes occurring in almost all the major systems and organs of the human body resulting in serious physical and mental disturbances and also posing tremendous burden on the health care resources of the country. The common sites of involvement include cardiovascular system, nervous system (central and peripheral), eyes, gastrointestinal system, genitourinary system, nasal and paranasal sinus region, hepatopancreatobiliary system, etc. Radiological manifestations are directly proportional to the duration and severity of involvement of the various systems. Various imaging (diagnostic and invasive) techniques can be used to detect the various manifestations as well as subsequent complications occurring during the course of disease. The following imaging techniques can be utilized for the purpose of evaluating the patients of DM: • Radiography  • Special investigations • Ultrasonography (USG) and color doppler study (including echocardiography - ECHO] • Computed tomography (CT) • Magnetic resonance imaging (MRI) • Radionuclide scintigraphy (including single photon emission computed tomography - SPECT)